Inkjet printing of resistively loaded FSS for microwave absorbers. Issue 13 (3rd June 2015) - Zabri, S.N.; Cahill, R.; Conway, G.; Schuchinsky, A.
Abstract : Inkjet printing is proposed as a means to create the resistively loaded elements of a frequency selective surface (FSS) which suppresses radar backscatter when placed above a metal ground plane. Spectral transmission and reflection measurements from 9 to 18 GHz show that the dot density of the printed features and the volume ratio of an aqueous vehicle and nano‐silver (Ag) ink mixture can be selected to obtain surface resistances in the range 1.2–200 Ω/sq.